She-Coronavirus: How cartoonists reflected women health workers during the COVID-19 pandemic. Issue 2 (May 2022) - Domínguez, Martí; Sapiña, Lucía
Women account for 70% of healthcare workers, so their role has been – and still is – fundamental in addressing and managing the current pandemic event caused by the SARS-CoV-2 coronavirus. Far from being an opportunity to highlight the importance of women in the field, the healthcare crisis, together with lockdown policies and care responsibilities, have contributed to increase the gender gap. To study the depiction of women healthcare professionals, this paper analyses 401 cartoons on the COVID-19 pandemic that depict healthcare workers. Most represent doctors as men and nurses as women, in roles subordinate to men. The representation of women is also impacted by stereotypes that do not contribute to better reflect the roles and professional skills of women in the healthcare field today.